Corneal status following modified Blumenthal technique of manual small incision cataract surgery (MSICS) compared to phacoemulsification in treatment of grade III or more nuclear sclerosis-cohort study - Jain, K; Malik, K PS; Gupta, S (Nepalese Journal of Ophthalmology, 2015)
Objective: To evaluate the endothelial cell loss and central corneal thickness in modified Blumenthal technique of MSICS and Phacoemulsification. Method: A prospective study in which 50 cases of nuclear sclerosis grade III (LOCS III) or more were randomized in two groups of 25 each. Group A underwent modified Blumenthal MSICS. Lens expression was facilitated by viscoelastic injection through ACM and scleral pressure by iris repositor. Group B underwent 2.8 mm phacoemulsi¿cation. Specular microscopy and pachymetry were done at 1st POD, 1st, 3rd and 6th week. Results: No significant difference in endothelial cell loss and central corneal thickness between group A and group B (p > 0.05) was found. Conclusion: This technique of MSICS is not inferior, an innovative, safe and highly effective in hard cataracts.